Pengaruh Media Sosial terhadap Peningkatan Kejahatan Siber di Indonesia - Klarisa Desi Ananta; Triyo Ambodo; Agus Tohawi (Bahasa Indonesia, 2024)
The use of social media in Indonesia has significantly increased, providing a platform for individuals to interact and share information. However, this increase is accompanied by a rise in cybercrime, including online fraud, identity theft, and cyberbullying. This study aims to analyze the influence of social media on the increase of cybercrime in Indonesia, focusing on the factors that contribute to users' vulnerability. Data shows that the lack of digital literacy and critical thinking skills among social media users is a primary cause of the increasing risk of cybercrime. Additionally, social media algorithms that display content based on user preferences can exacerbate the problem of spreading false and manipulative information. Therefore, collaborative efforts between the government, private sector, and society are needed to raise awareness of digital security and establish stronger regulations to protect users from cyber threats